pH, alkalinity, temperature, salinity and other variables collected from discrete sample and profile observations using CTD, bottle and other instruments from the THALASSA in the North Atlantic Ocean from 2004-06-04 to 2004-07-06 (NODC Accession 0113918) (NOAA NCEI Environmental Data Archive, 2016)
NODC Accession 0113918 includes chemical, discrete sample, physical and profile data collected from THALASSA in the North Atlantic Ocean from 2004-06-04 to 2004-07-06 and retrieved during cruise CARINA/35TH20040604 and OVIDE 2004. These data include ALKALINITY, DISSOLVED OXYGEN, HYDROSTATIC PRESSURE, NITRATE, PHOSPHATE, Potential temperature (theta), SALINITY, SILICATE, WATER TEMPERATURE and pH. The instruments used to collect these data include CTD and bottle. These data were collected by F. Perez, M. Alvarez, M. Castano and Aida F. Rios of Instituto de Investigaciones Marinas de Vigo and T. Huck [affiliation unknown] as part of the CARINA/35TH20040604, OVIDE 2004 data set. The CARINA (CARbon dioxide IN the Atlantic Ocean) data synthesis project is an international collaborative effort of the EU IP CARBOOCEAN, and U.S. partners. It has produced a merged internally consistent data set of open ocean subsurface measurements for biogeochemical investigations, in particular, studies involving the carbon system. The original focus area was the North Atlantic Ocean, but over time the geographic extent expanded and CARINA now includes data from the entire Atlantic, the Arctic Ocean, and the Southern Ocean.